KOMPETENSI ADVOKAT SYARIAH DALAM PENANGANAN PERKARA PERDATA DAN PIDANA DI KOTA KENDARI - Rachmadani Rachmadani (IAIN Kendari, 2019)
Although there has been juridical recognition through prevailing legal regulations, there are still some parties who doubt the existence of advocates of Sharia Faculty graduates as professional advocates. It is based on the assumption of the lack of technical law competence owned by shariah lawyer, then it is so risky to lawy in the judicial process. Based on this issue, the competent which is possessed by shariah advocate become attractive to be inquired through performing the process of practical law. This research is a qualitative research in which object of study is the competence of sharia lawyer in handling civil and criminal case. Result of the research indicated that in Kendari City, the existence of sharia advocate is in two place which are LBH HAMI and Law Office of Murtado which counted 10 people. Shariah lawyers exist to provide legal services for the community in solving various problems. Related to the competence of sharia lawyers, if it judge from its legal practice in handling civil and criminal cases in Kendari City, it can be said that it has been able to apply legal knowledge from formal aspect (lawyer) and material well according to the provisions of Law no. 18 in 2003 on Advocates. In addition, shariah lawyers also have more valuesthan lawyer in general, which is able to apply Islamic philosophical values in providing legal services to clients.